Miraculous healing in the book of Tobit - Henderson, Ruth (Journal for the study of the pseudepigrapha, 2024)
Much academic research has been conducted on the rich and bewildering variety of sources underlying the book of Tobit. In this study, yet another literary type from the Hebrew Bible which has received little scholarly attention will be suggested. In Part 1 of the following study, “the prophetic miracle story,” found among the historical traditions of Northern Israel in 2 Kgs 1–8, will be investigated according to its characteristic features. The correspondence between these features and those of the accounts of the miraculous healings of Sarah and Tobit in the book of Tobit will then be demonstrated, and it will be suggested that this literary type forms a model for the accounts of the healing of Tobit and Sarah in the book of Tobit. In addition to this, the influence of other themes from 2 Kgs 1–8 on the book of Tobit will be proposed. In Part 2 of this study, certain attested forms of healing from the author’s Hellenistic cultural background will be investigated. It will be suggested the book of Tobit could represent the author’s response to these Hellenistic types of healing in the revival and development of the earlier prophetic miracle story from 2 Kgs 1–8.